Late-life restoration of mitochondrial function reverses cardiac dysfunction in old mice - Chiao, Ying Ann; Zhang, Huiliang; Sweetwyne, Mariya; Whitson, Jeremy; Ting, Ying Sonia; Basisty, Nathan; Pino, Lindsay K; Quarles, Ellen; Nguyen, Ngoc-Han; Campbell, Matthew D; Zhang, Tong; Gaffrey, Matthew J; et al. (eLife, 2020)
Diastolic dysfunction is a prominent feature of cardiac aging in both mice and humans. We show here that 8-week treatment of old mice with the mitochondrial targeted peptide SS-31 (elamipretide) can substantially reverse this deficit. SS-31 normalized the increase in proton leak and reduced mitochondrial ROS in cardiomyocytes from old mice, accompanied by reduced protein oxidation and a shift towards a more reduced protein thiol redox state in old hearts. Improved diastolic function was concordant with increased phosphorylation of cMyBP-C Ser282 but was independent of titin isoform shift. Late-life viral expression of mitochondrial-targeted catalase (mCAT) produced similar functional benefits in old mice and SS-31 did not improve cardiac function of old mCAT mice, implicating normalizing mitochondrial oxidative stress as an overlapping mechanism. These results demonstrate that pre-existing cardiac aging phenotypes can be reversed by targeting mitochondrial dysfunction and implicate mitochondrial energetics and redox signaling as therapeutic targets for cardiac aging.